Application of Flood Hazard Index and Multi-Criteria Decision Analysis to Determine the Effect of Urbanization on Flood Hazard Areas in the City of Jijel, Algeria - Chabou, Omayma; Lazri, Youcef; Lehtihet, Mohammed Chérif (Indonesian Journal of Social Science Research, 2024)
This research aims to study the effect of urbanization on flood-prone areas in the city of Jijel. The methods used in the study are (i) generation of a susceptibility map (ii) identification of land-use maps for the years 1988 and 2021 (iii) generation of flood hazard maps for the years 1988 and 2021. The determination of flood hazard areas is mainly based on an index approach. Using the ArcGIS raster calculator tool, the susceptibility map was multiplied by the land use map to generate a flood hazard index. Based on parameter weights derived from the Analytical Hierarchical Process (AHP) approach, the various flow accumulation maps, slope, distance to stream, elevation and geological parameters were combined to create the flood susceptibility map. The effects of urbanization on flood-prone areas were determined by overlaying the susceptibility map with two land-use maps from 1988 and 2021. The results show that while areas at very low, low and moderate risk decreased by 9.28%, 17.31% and 47.3%, respectively, areas at high and very high risk increased by 32.36% and 41.53%, respectively. The study showed that increases in the high zone were mainly due to uncontrolled urban development, mainly caused by rural exodus in Algeria's coastal cities.